(untitled) (Bangladesh Agronomy Journal, 2020)
Dry-seeded rice (DSR) is a labor and water saving emerging production system. The use of pre-emergence herbicides was found to be the most effective weeds control measure under the DSR system. Although several herbicides are now available in market, the selection of right herbicides with a time of application is crucial for effective control of weeds as well as to reduce the phyto toxicity of crops. A field study in a split-plot design with three replications was conducted to evaluate the effect of application time of soil applied herbicides (viz., 3 times - before crop sowing, after crop sowing but before the first irrigation, and after sowing and first irrigation) and four weeding regimes (viz., weed free, partial-weedy, herbicide oxadiargyl 80 g ai ha-1, and pendimethalin 1000 g ai ha-1) on weed control efficacy, crop performance as well as phytotoxicity of applied herbicides under DSR system. Rice plant stand establishment was highly influenced by application time of herbicides and weeding regimes. Application of pendimethalin at 1000 g ai ha-1 significantly reduced the density of rice plant, more so as sowing was advanced. Compared with the non-treated (partial-weedy) treatment (190 to 195 rice plants m-2), pendimethalin application before sowing, after sowing but before irrigation, and after sowing and irrigation reduced rice plant density by 48, 25 and 12%, respectively. While no significant difference was observed on plant density due to the application of oxadiargyl 80 g ai ha-1, regardless of application time. In case of weed control efficacy for individual herbicides, pendimethalin effectively controlled weeds even spraying before sowing and irrigation; but comparatively less effective than spraying after irrigation. In controlling weeds, oxadiargyl was only effective when spraying after sowing and irrigation, but not before irrigation. Grain yield was significantly increased as the time of herbicide was delayed from before sowing (2.2-2.4 t ha-1), after sowing but before irrigation (2.5-2.6 t ha-1), and after sowing and irrigation (4.0-4.1 tha-1). The results suggest that pre-emergence herbicides should be applied after sowing and irrigation for controlling weeds effectively and also reduce crop toxicity under the DSR system. Bangladesh Agron. J. 2019, 22(1): 15-25